Toxicity profiles between strains of Alexandriumtamiyavanichii - Hamdan, Nurul Ashima; Abu Hassan, Muhamad Shafiq; Abd Hamid, Shafida; Mohammad Noor, Normawaty; Muhamad Bunnori, Noraslinda (Institute of Research and Journals, 2018)
Phycotoxins are byproducts of toxic microalga that capable of causing severity on humans upon consuming contaminated seafood. The amount of toxins released by microalgae varies according to species as some of the microalgae synthesize toxins within small number of cells while others required a blooming event for the toxins to be detected. It is also possible for the toxicity of one species being gradually decreases throughout years in culture. Alexandrium tamiyavanichiihas been reported to cause toxicity in seafood products that subject to hospitalized cases in Malaysia. Genus Alexandrium has been known for its stability in producing toxins yet no total loss of toxicity has been recorded. Two cultures of A.tamiyavanichii have been tested for its toxicity using high-performance liquid chromatography (HPLC) with GTX standards as reference. Strains isolated from Kuantan Port during recent cases of paralytic shellfish poisoning (PSP) outbreak showed extremely high in total toxin content (3.07 nmol.cell-1) while the clonal culture of A. tamiyavanichii established from Sebatu Malacca exhibited very low level of toxicity (1.167 fmol.cell-1). There are many factors influencing toxicity properties of A. tamiyavanichii with highlights in nutrients deprivation and adaptation as well as bacterial influences for the aged culture.